(untitled) (ModaPalavra e-periódico, 2008)
This article presents ’Santa Catarina Contemporary Fashion project’ (SCMC) on an approach anchored in: interinstitutional cooperation, "full company" concept, and, the University as an institution open and committed to the management of shared knowledge. From this approach, it’s possible to conclude that the ef ective cooperation of the knowledege exchange among education and business institutions, and the exercise of working together, have been some of the major contributions of the project SCMC for design promotion in Santa Catarina.